Characterization of adolescents with diabetes mellitus attended in ambulatory of teaching hospital - Caren da Silva Bertoldo; Júlia Heinz da Silva; Andressa da Silveira; Aline Cammarano Ribeiro; Jaquiele Jaciara Kegler; Eliane Tatsch Neves (Universidade Federal de Santa Maria, 2019)
Objective: to characterize the sociodemographic and clinical profile of adolescents with diabetes mellitus attended in an outpatient clinic of a teaching hospital. Method: exploratory descriptive research with quantitative approach. Data was analyzed using descriptive statistics. Results: 45 medical records of adolescents were analyzed, most of them male (53.3%), diagnosed with type I diabetes mellitus (95.6%), and demand for medication care associated with modified habitual care (73.4%), 90.7% of them was using insulin, and 68.9% who already needed hospitalization. All were followed up with in specialized clinics. We emphasized the search for emergency services over than primary health care. Conclusions: The sociodemographic and clinical characterization of these adolescents pointed out the continuous demands of care that adolescents need to maintain their health. Therefore, it is important to follow-up the adolescents, in order to help them in the process of coping with the disease.